2013
DOI: 10.1186/1743-7075-10-48
|View full text |Cite|
|
Sign up to set email alerts
|

Carnitine supplementation to obese Zucker rats prevents obesity-induced type I to type II muscle fiber transition and favors an oxidative phenotype of skeletal muscle

Abstract: BackgroundIn the present study, we tested the hypothesis that carnitine supplementation counteracts obesity-induced muscle fiber transition from type I to type II.Methods24 obese Zucker rats were randomly divided into two groups of 12 rats each (obese control, obese carnitine) and 12 lean Zucker rats were selected for lean control group. A control diet was given to both control groups and a carnitine supplemented diet (3 g/kg diet) was given to obese carnitine group for 4 wk. Components of the muscle fiber tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
6
29
0
Order By: Relevance
“…It is well known that the carnitine status in obese Zucker rats and other models of genetic and diet-induced obesity is markedly impaired and as a consequence several metabolic disturbances are induced [3133]. In contrast, supplementation with carnitine improves carnitine status, which was also demonstrated in the present study, and reverses to a great part these metabolic disturbances, like elevated blood levels of triacylglycerides and non-esterified fatty acids, glucose intolerance and insulin resistance [3032, 34]. The key finding of the present study is that carnitine supplementation resulted in a profound change in the miRNA expression profile in skeletal muscle of obese Zucker rats suggesting a novel regulatory mechanism by which dietary carnitine alters gene expression and mediates at least some of its biological effects.…”
Section: Discussionsupporting
confidence: 80%
“…It is well known that the carnitine status in obese Zucker rats and other models of genetic and diet-induced obesity is markedly impaired and as a consequence several metabolic disturbances are induced [3133]. In contrast, supplementation with carnitine improves carnitine status, which was also demonstrated in the present study, and reverses to a great part these metabolic disturbances, like elevated blood levels of triacylglycerides and non-esterified fatty acids, glucose intolerance and insulin resistance [3032, 34]. The key finding of the present study is that carnitine supplementation resulted in a profound change in the miRNA expression profile in skeletal muscle of obese Zucker rats suggesting a novel regulatory mechanism by which dietary carnitine alters gene expression and mediates at least some of its biological effects.…”
Section: Discussionsupporting
confidence: 80%
“…In adult rodents, insulin resistance in skeletal muscle is associated with an increased prevalence of type IIb muscle fibers . In the current study, MHC type I fiber protein and mRNA levels were increased in the gastrocnemius muscle of OLETF‐C rats compared with LETO‐C rats ( P < 0.05; Figure C).…”
Section: Discussionsupporting
confidence: 52%
“…D, Comparison between mean values of the area percentage of MHC type IIa among the studied groups. 46 Crunkhorn et al 47 demonstrated that reduced expression of PGC-1α in skeletal muscle of HFD-induced obesity is attributed to muscle insulin resistance and excess nutrients especially fatty acids, also, insulin enhanced the expression of PGC-1α in human skeletal muscles and this expression was positively related to glucose uptake and oxidation. HFD, high-fat diet; MHC, myosin heavy chain muscle.…”
Section: Discussionmentioning
confidence: 99%